Uniform spectral representation of the Earth’s inner density structures and their gravitational field - TENZER, Robert; NOVÁK, Pavel; VAJDA, Peter (Contributions to Geophysics and Geodesy, 2011)
We introduce the generic expressions for computing the gravitational field (potential and its radial derivative) generated by an arbitrary density (contrast) layer with a variable depth and thickness having a laterally-distributed radial density variation. The information on the geometry and density distribution of a volumetric mass layer is described by means of spherical harmonics. These generic expressions can uniformly be applied to model all major known density structures within the Earth’s interior using methods for a spherical harmonic analysis and synthesis of the gravitational field. This is demonstrated on specific examples given for various density models commonly adopted for the approximation of crust density structures.